Maritime Networks, Port Efficiency, and Hinterland Connectivity in the Mediterranean - Arvis, Jean-François; Vesin, Vincent; Carruthers, Robin; Ducruet, César; de Langen, Peter (Washington, DC: World Bank, 2018)
For millennia, the Mediterranean has been one of the most active trading areas, supported by a transport network connecting riparian cities and beyond to their hinterland. The Mediterranean has complex trade patterns and routes--but with key differences from the past. It is no longer an isolated world economy: it is both a trading area and a transit area linking Europe and North Africa with the rest of the world through the hub-and-spoke structure of maritime networks.